STRATEGI GURU DALAM MENGHADAPI GAYA BELAJAR SISWA PADA MAPEL MATEMATIKA KELAS VI SDN KREBET - Istiqomah; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study discusses the relationship between students' learning styles and teaching strategies applied by teachers in mathematics learning for sixth grade students at Krebet Elementary School. There are three different learning styles, namely visual, auditory and kinesthetic, which affect students' understanding and interest in mathematics learning. To accommodate this diversity, teachers use active learning strategies, involve teaching aids, implement peer tutors, and create a supportive learning environment. This research method uses qualitative techniques through observation and interviews. The results of this study indicate that using strategies that are adjusted to each student's learning style can improve student achievement and learning outcomes. The use of visual media is beneficial for students with visual learning styles, discussions are effective for auditory students, while direct activities are suitable for kinesthetic students. In addition, the involvement of peer tutors has been shown to help clarify students' understanding of the material. Learning mathematics in this context not only requires intellectual improvement and skills to solve problems, but also shapes students' personalities. The materials studied include numbers, geometry, measurement, and data processing. Overall, this study concludes that understanding students' learning styles combined with appropriate teaching strategies can create an effective and enjoyable learning process, and significantly improve students' mathematics learning outcomes.